PENGEMASAN PEMBELAJARAN TARI MANDUDA BERBASIS E-LEARNING SCHOOLOGY UNTUK SISWA KELAS X SEKOLAH MENENGAH ATAS - Bella Kurniati; Yusnizar Heniwaty (Gesture: Jurnal Seni Tari, 2020)
ABSTRACTThis study aims to describe the steps of packaging learning materials for Manduda Dance based on E-Learning Schoology. The theoretical foundation in this study is used as a guideline in data collection consisting of learning theory, packaging, learning media, and E-Learning Schoology, which are used as a reference in the packaging of this research. The method used in this research is quantitative qualitative method. The population is students of SMA 10 Medan, while the research sample is 10 students of class X SMA Negeri 10 Medan. Data collection techniques are carried out by means of observation, interviews, literature studies, documentation, and research instruments that use a questionnaire to test the feasibility of media experts and material experts and data analysis techniques. This data is then analyzed using quantitative qualitative methods. The results of this study are the packaging of Manduda dance learning material which is packaged into an audio visual media based on E-Learning schoology in accordance with the theory used. The packaging steps in this study use 4 stages: (1) Identification of Needs (2) Formulation of Objectives (3) Formulation of Material Items (4) Making Flowcharts, Finishing and Programming. At the design validation stage, this product involves 2 people validating the material, 2 people validating the media expert, and 10 students for the user trial. Scores obtained from the validation and user trials get very good categories with a detailed score of 4.6 from the material expert validation trial, a score of 4.7 from the media expert validation test and a 4.3 score from the user trial. The score proves that this learning video product is feasible to be applied in the learning process of Culture and Arts Class X Senior High School, this learning video product is packaged into audio visual media then uploaded in the E-Learning Schoology application that is used by utilizing the internet network. However, the learning video can still be used without an internet network by uploading it into a CD / DVD Room, flashdisk and so on. Keywords: Packaging, E-learning Schoology, Manduda Dance. ABSTRAKPenelitian ini bertujuan untuk mendeskripsikan langkah-langkah pengemasan materi pembelajaran Tari Manduda berbasis E-Learning Schoology. Landasan teoritis dalam penelitian ini dijadikan pedoman dalam pengumpulan data terdiri dari teori pembelajaran, pengemasan, media pembelajaran, dan E-Learning Schoology, yang dijadikan acuan dalam pengemasan penelitian ini. Metode yang digunakan dalam penelitian ini adalah metode kualitatif kuantitatif. Populasinya adalah siswa-siswi SMA Negeri 10 Medan, sedangkan sampel penelitiannya adalah 10 orang siswa-siswi kelas X SMA Negeri 10 Medan. Teknik pengumpulan data dilakukan dengan cara observasi, wawancara, studi kepustakaan, dokumentasi, dan instrument penelitian yang menggunakan angket untuk uji kelayakan ahli media dan ahli materi dan teknik analisis data. Data ini kemudian dianalisis dengan metode kualitatif kuantitatif. Hasil penelitian ini adalah Pengemasan materi pembelajaran tari Manduda  yang dikemas kedalam bentuk media audio visual berbasis E-Learning schoology sesuai dengan teori yang digunakan. Langkah-langkah pengemasan dalam penelitian ini menggunakan 4 tahap yaitu ,(1) Identifikasi Kebutuhan (2) Perumusan Tujuan (3) Perumusan Butir-Butir Materi (4) Pembuatan Flowchart, Finishing  dan Pemprograman. Pada tahap validasi desain, produk ini melibatkan 2 orang validasi ahli materi, 2 orang validasi ahli media, dan 10 orang siswa untuk uji coba pengguna. Skor yang didapat dari validasi dan uji coba pengguna mendapat kategori sangat baik dengan rincian skor 4,6 dari uji coba validasi ahli materi, skor 4,7 dari uji validasi ahli media dan skor 4,3 dari uji coba pengguna. Skor tersebut membuktikan bahwa produk video pembelajaran ini layak untuk diterapkan dalam proses pembelajaran Seni Budaya kelas X Sekolah Menengah Atas, produk video pembelajaran ini dikemas kedalam bentuk media audio visual kemudian diunggah dalam aplikasi E-Learning Schoology yang digunakan dengan memanfaatkan jaringan internet. Namun, video pembelajaran tersebut masih bisa dimanfaatkan tanpa jaringan internet dengan mengunggahnya kedalam CD/DVD Room, flashdisk dan sebagainya . Kata kunci : Pengemasan, E-learning Schoology, Tari Manduda.